Mechanism research of slip effect between frictional laminated beams. (March 2019) - Zhong, Jintu; Yan, Quansheng; Wu, Jie; Zhang, Zhuojie
For laminated beams connected by Coulomb friction, interlayer slippage occurs when interfacial shear stress exceeds the resistant friction stress. Then, the physical properties of the laminated beams will change and may even cause structural damage. In this article, the law of interlayer slippage of laminated beams is obtained by mechanical derivation, and the finite element model is used for comparison verification. First, the internal shear force calculation formula of the laminated beam considering the interlaminar friction is derived from the segment micro-element method. Second, interlayer slippage laws of the frictional laminated beams in both horizontal and longitudinal direction are derived according to the hierarchical slip determination conditions. Third, according to the state quantity of different boundary conditions, the transfer matrix method is used to solve the longitudinal length of interlayer slip. Then, the design of the algorithm program is completed by MATLAB. Finally, based on the comparison between the finite element model calculation results and the calculation results of the algorithm program, the accuracy of the proposed method is verified. The analysis results indicate that slippage destroys the integrity of the laminated beam section and reduces the bending moment of inertia of the slip section of the beam. The influence of slip effect on the frictional laminated beams should be considered in deflection calculation.